Buruli Ulcer Mycobacterium Ulcerans Disease - Pluschke, Gerd; Röltgen, Katharina (Springer International Publishing : Imprint: Springer, 2019)
A major objective of this open access book is to summarize the current status of Buruli Ulcer (BU) research for the first time. It will identify gaps in our knowledge, stimulate research and support control of the disease by providing insight into approaches for surveillance, diagnosis, and treatment of Buruli Ulcer. Book chapters will cover the history, epidemiology diagnosis, treatment and disease burden of BU and provide insight into the microbiology, genomics, transmission and virulence of Mycobacterium ulcerans.